Electrical Discharge Machining Flyback Converter using UC3842 Current Mode PWM Controller - Nazriah Mahmud; Azli Yahya; Trias Andromeda (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper presents a current mode Pulse Width Modulation (PWM) controlled Flyback converter using UC3842 for Electrical Discharge Machining current generator control circuit. Circuit simplicity and high efficiency can be achieved by a Flyback converter with current mode PWM controller. The behaviors of the system's operation is analyzed and discussed by varying the load resistance. Matlab software is used to simulate the Flyback converter where a prototype has been built and tested to verify it's performance.